PENGEMBANGAN LKS UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM PEMBELAJARAN REALISTIK - Hanizar Sary (Universitas Negeri Medan, 2019)
This study aims to determine validity of Student Worksheet developed with realistic learning. This research is a development research based on the Thiagarajan 4-D model. The subjects in this study were students of class VIII at MTs Negeri 2 Medan. While the object in this study is the Student Worksheet (LKS) with realistic learning in the material of the Two Variable Linear Equation System. The instruments used were the worksheets that had been developed, the pre-test mathematical communication skills test consisted of 5 Essay questions and Posttest 5 Essay questions, the student questionnaire responses amounted to 30 questions. Data obtained from research instruments were analyzed using the N-Gain formula. There are research results showing There is an increase in students' communication skills through worksheets developed with realistic learning. The results of the pre trial I test is 62.03, an increase in the pre test II trial is 68.23, and the results of the post I trial test is 67.43, an increase in the post trial II is 77.9. Furthermore, the N-Gain trial I 0.14 increased to 0.30, meaning that there was an increase in students' mathematical communication skills after using the worksheet developed from the criteria of low to moderate.Keywords: Realistic Learning, Students' Communication Ability